Polybrominated diphenyl ethers—plasma levels and thyroid status of workers at an electronic recycling facility - Julander, A.; Karlsson, M.; Hagström, K.; Ohlson, C. G.; Engwall, M.; Bryngelsson, I-L.; Westberg, H.; van Bavel, B. (International archives of occupational and environmental health, 2005)
Personnel working with electronic dismantling are exposed to polybrominated diphenyl ethers (PBDEs), which in animal studies have been shown to alter thyroid homeostasis. The aim of this longitudinal study was to measure plasma level of PBDEs in workers at an electronic recycling facility and to relate these to the workers' thyroid status. PBDEs and three thyroid hormones: triiodothyronine (T(3)), thyroxin (T(4)) and thyroid stimulating hormone (TSH) were repeatedly analysed in plasma from 11 workers during a period of 1.5 years. Plasma levels of PBDEs at start of employment were <0.5-9.1 pmol/g lipid weight (l.w.). The most common congener was PBDE #47 (median 2.8 pmol/g l.w.), followed by PBDE #153 (median 1.7 pmol/g l.w.), and PBDE #183 had a median value of <0.19 pmol/g l.w. After dismantling the corresponding median concentrations were: 3.7, 1.7 and 1.2 pmol/g l.w., respectively. These differences in PBDE levels were not statistically significant. PBDE #28 showed a statistically significantly higher concentration after dismantling than at start of employment (P=0.016), although at low concentrations (start 0.11 pmol/g l.w. and dismantling 0.26 pmol/g l.w.). All measured levels of thyroid hormones (T(3), T(4) and TSH) were within the normal physiological range. Statistically significant positive correlations were found between T(3) and #183 in a worker, between T(4) and both #28 and #100 in another worker and also between TSH and #99 and #154 in two workers. The workers' plasma levels of PBDEs fluctuated during the study period. Due to small changes in thyroid hormone levels it was concluded that no relevant changes were present in relation to PBDE exposure within the workers participating in this study.